2013
DOI: 10.1080/15374416.2013.843464
|View full text |Cite
|
Sign up to set email alerts
|

Low Vagal Tone Magnifies the Association Between Psychosocial Stress Exposure and Internalizing Psychopathology in Adolescents

Abstract: Vagal tone is a measure of cardiovascular function that facilitates adaptive responses to environmental challenge. Low vagal tone is associated with poor emotional and attentional regulation in children and has been conceptualized as a marker of sensitivity to stress. We investigated whether the associations of a wide range of psychosocial stressors with internalizing and externalizing psychopathology were magnified in adolescents with low vagal tone. Resting heart period data were collected from a diverse com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
97
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 113 publications
(158 reference statements)
22
97
7
Order By: Relevance
“…The importance of differentiating between contributions of the SNS and PNS is underscored by our finding that only SNS indicators are associated with exposure to threat. In contrast, in previous studies we (and others) have found that PNS reactivity to psychosocial stress functions as a moderator, such that risk of internalizing psychopathology following exposure to CAs varies as a function of PNS activity (71,72). Taken together, these results suggest that measures of ANS activity, particularly of the SNS, may be used as a clinically useful index of stress sensitivity following exposure to violence in childhood alongside commonly used HPA-axis measures such as cortisol.…”
Section: Discussioncontrasting
confidence: 89%
“…The importance of differentiating between contributions of the SNS and PNS is underscored by our finding that only SNS indicators are associated with exposure to threat. In contrast, in previous studies we (and others) have found that PNS reactivity to psychosocial stress functions as a moderator, such that risk of internalizing psychopathology following exposure to CAs varies as a function of PNS activity (71,72). Taken together, these results suggest that measures of ANS activity, particularly of the SNS, may be used as a clinically useful index of stress sensitivity following exposure to violence in childhood alongside commonly used HPA-axis measures such as cortisol.…”
Section: Discussioncontrasting
confidence: 89%
“…McLaughlin, Rith-Najarian, Dirks, and Sheridan (2015) examined both vagal tone (RSA) and a variety of contextual stressors (e.g., community violence, victimization, traumatic events) in relation to internalizing and externalizing symptoms in adolescence. For internalizing symptoms only, the researchers reported significant interactions between low vagal tone and a number of contextual stressors such that stressors were associated with more internalizing symptoms (anxiety and depression) among adolescents with lower vagal tone, but not higher vagal tone.…”
Section: Gender Differences In Associations Between Vagal Suppressionmentioning
confidence: 99%
“…It is a time of accelerated growth across many social, psychological, and biological domains, as well as a period of increased vulnerability (Dahl, 2004; Steinberg et al, 2006). Some research suggests that stress is more likely to have emotional consequences in the early years of adolescence than prior to that time (Larson & Ham, 1993; McLaughlin, Rith-Najarian, Dirks, & Sheridan, 2015), perhaps due to better cognitive understanding of stressful events (Larson & Ham, 1993; McLaughlin et al, 2015) or perhaps because of the co-occurrence of many transitional changes (Simmons & Blyth, 1987). Stress reactivity appears to be heightened during times of pubertal development (Romeo, 2010; Spear, 2009).…”
mentioning
confidence: 99%
“…Using this approach, researchers gather reports from those involved in family interactions (e.g., parents and adolescents). Multiple informants' reports may also be augmented by data from other sources, such as independent observers' ratings of family interactions (e.g., level of warmth or hostility displayed within a laboratory-based family discussion task; De Los Reyes et al 2015b), or direct assessments of physiological processes as they manifest within relevant contexts (e.g., elevations in arousal or decreased physiological flexibility displayed during computer-based tasks, unstructured home observations, periods of social stress, or a resting period; Aldao and De Los Reyes 2015;De Los Reyes et al 2015a;De Los Reyes and Aldao 2015;Cohen et al 2015;Franklin et al 2015;Leitzke et al 2015;McLaughlin et al 2015;Youngstrom and De Los Reyes 2015). Further, a key focus of this approach involves collecting assessments of psychosocial outcomes commonly linked to family functioning, such as adolescent psychosocial functioning, which may also leverage multi-informant, multi-method measurement approaches (e.g., reports of adolescents' mental health from adolescents, parents, teachers, clinicians, and independent observers).…”
Section: Introductionmentioning
confidence: 99%